A study of academic entrepreneurs using venture capital data - Junfu Zhang (Institute for the Study of Labor (IZA), 2007)
Academic entrepreneurship has become an increasingly important channel through which universities contribute to economic development. This paper studies academic entrepreneurs using a comprehensive venture capital database. I find that about two-thirds of the academic entrepreneurs locate their businesses in the same state as their universities. National academy membership and number of faculty awards, measures of a university's research quality, are the most significant variables in explaining the number of academic entrepreneurs from a university. In contrast, the abundance of venture capital near the university has no significant effect on academic entrepreneurship.
Keywords: 330; Unternehmer; Forschungskooperation; Unternehmensgründung; Risikokapital; Akademische Berufe; Betriebsaufspaltung; USA